Numerical Solution of Problem for Non-Stationary Heat Conduction in Multi-Layer Bodies - R. I. Esman; V. A. Ustimovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2007)
A mathematical model for non-stationary heat conduction of multi-layer bodies has been developed. Dirac’s δ-function is used to take into account phase and chemical transformations in one of the wall layers. While formulating a problem non-linear heat conduction equations have been used with due account of dependence of thermal and physical characteristics on temperature. Solution of the problem is realized with the help of methods of a numerical experiment and computer modeling.